Ergonomic Analysis of Small-Scale Palm Sugar Starch Processing Industry in Rancakalong Village, Sumedang Regency - Nanda, Muhammad Achirul; Thoriq, Ahmad; Arum, Marsya Sekar (PERTETA, 2024)
Rancakalong village, Sumedang Regency, has been known for its small-scale palm sugar starch processing industry since 2013. This industry produces starch from palm trees, which is crucial for food and beverages. Generally, the processes involved in processing palm sugar starch include (i) splitting of the palm, (ii) grating, (iii) coarse fiber screening, (iv) fine fiber screening, (v) harvesting, and (vi) drying. Initial evaluations indicated that the workers experienced physical discomfort during their work. Therefore, this study aimed to analyze the ergonomic aspects of processing palm sugar starch, including the working posture, standard time, workload, noise, and vibration. Based on the analysis, the risk level for each work element in processing palm sugar starch fell into the high-risk (score 8-10) and very high-risk (score 11-15) categories. These risks cause discomfort due to inappropriate work posture and duration, necessitating significant changes. The standard time required for each work element was as follows: 212.88±28.43 seconds/kg (palm splitting), 363.45±12.90 seconds/kg (grating), 95.08±9.74 seconds/kg (coarse fiber screening), 192.05±21.27 seconds/kg (fine fiber screening), 35.57±5.78 seconds/kg (harvesting), and 1821.01±41.09 seconds/kg (drying). Regarding workload analysis, processing palm sugar starch activities fell into the moderate category with total energy cost (TEC) values ranging from 92.66±1.50 265.55±3.88 kcal/hour. Regarding noise and vibration analysis, the grating work element was identified as the station with the highest exposure, i.e., 96.00±0.82 dB and 1.6±0.05 m/s2, respectively. The results of this study could be used as a basis for developing more efficient work procedures, maintaining health, and improving safety in the processing of palm sugar starch.